Quranic concept of halalan tayyiban and its application in food and beverages of hospitality sector in Malaysia / Amiratul Munirah Yahaya and Zulaipa Ruzulan - Yahaya, Amiratul Munirah; Ruzulan, Zulaipa (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2020)
Halal hospitality services have been increasing year by year due to the demand from Muslims for halal food and beverages. With this development, there is a need to ensure that the halal food providers are well-equipped enough with halal knowledge in order to ensure Muslim consumers obtain halal food in the best manner. This is because malpractice could happen if the practitioners are having lack of knowledge on halal related matter. In relation to this, this article aims to discuss the Quranic concept of halalan tayyiban and its application in food and beverage in the hospitality sector in Malaysia. Firstly, the study aims to examine the Quranic principles of halalan tayyiban. Secondly, it takes into account to what extent that these Quranic principles are applied in the hospitality sector of Malaysia, hence, these principles are examined and analysed accordingly. The methods of data collection involved library research and in-depth interview with hospitality skills trainer. The technique of analysis used was content analysis. Data related to the study were analysed and descriptive data using percentages was used. The findings of the study indicated that some hotels are concerned with the Quranic concept of halalan tayyiban and it is applied in serving their food and beverage in order to attract more customers who are particular into taking halalan tayyiban food and beverage for healthy and righteous living.